2011
DOI: 10.1007/s12031-011-9567-6
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of P2 Nucleotide Receptors After Spinal Cord Injury Reduced the Gliotic Response and Spared Tissue

Abstract: Spinal cord injury (SCI) triggers a sequel of events commonly associated with cell death and dysfunction of glias and neurons surrounding the lesion. Although astrogliosis and glial scar formation have been involved in both damage and repair processes after SCI, their role remains controversial. Our goal was to investigate the effects of the P2 receptors antagonists, PPADS and suramin, in the establishment of the reactive gliosis and the formation of the glial scar. Molecular biology, immunohistochemistry, spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 76 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Preceding studies reported that the expression of P2X 4 and P2Y 2 receptors can be significantly increased during the acute and chronic stages of SCI (38,41). Here we analyzed the expression of P2X 4 , P2X 7 , P2Y 1 , and P2Y 4 transcripts at different times after induction of a severe traumatic lesion in the spinal cord of rats at T8 level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preceding studies reported that the expression of P2X 4 and P2Y 2 receptors can be significantly increased during the acute and chronic stages of SCI (38,41). Here we analyzed the expression of P2X 4 , P2X 7 , P2Y 1 , and P2Y 4 transcripts at different times after induction of a severe traumatic lesion in the spinal cord of rats at T8 level.…”
Section: Resultsmentioning
confidence: 99%
“…Although preceding approaches based on spinal cord-derived SPCs from either fetal or adult healthy donors reported only modest or no significant functional improvements during the acute phase of transplantation (31,34), we previously demonstrated that acute transplantation of epSPCis obtained from injured tissue reverses the paralysis associated with spinal cord contusion in rats (28). Moreover, a blockade of P2 nucleotide receptors after SCI reduces the gliosis response and spared tissue (38). Based on these findings, we studied whether epSPCi transplantation immediately after SCI is able to decrease P2X 4 and/or P2X 7 expression in the spinal cord of injured rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, the correlation between miR-363-5p and the P2X4 receptor contributes to the dedifferentiation and migration of Schwann cells after nerve injury [64]. In spinal cord injury (SCI), blockage of P2X7 receptors and other purinergic receptors provides neuroprotection in rats [65][66][67]. And a study holds that miR-135a is a potential therapeutic target for SCI because miR-135a downregulation causes overexpression of P2X7 receptors and increases excitotoxicity when exposed to the high concentration of ATP.…”
Section: Purinergic Signalling Modulated By Mirnas In Neurological Diseasesmentioning
confidence: 99%
“…Multiple purinergic receptors are expressed in the spinal cord (Apolloni et al, 2009), some of which become overexpressed after injury (Cavaliere et al 2003;Franke et al 2006;Rodríguez-Zayas et al 2010), including P2X 7 (Gómez-Villafuerteset al 2015;Schwab et al 2005). Blockage of P2X 7 and other purinergic receptors with either pyridoxalphosphate-6-azophenyl-2',4'-disulfonic acid (PPADS), oxidized ATP (oxo-ATP), brilliant blue G (BBG), or the partial agonist Ap 4 A provides neuroprotection in rat models of SCI (Peng et al 2009;Reigada et al 2017;Wang et al 2004;Rodríguez-Zayas et al 2011) and traumatic brain injury (TBI) (Wang et al 2015). Results indicate that blockage reduces neuronal damage, microglial activation, neutrophil infiltration and inflammatory response, leading to increased tissue preservation, although one study has failed to reproduce some of these effects (Marcilloet al 2012).…”
Section: Introductionmentioning
confidence: 99%